(untitled) (Latakia University Journal -Engineering Sciences Series, 2018)
The importance of integrating different communication technologies together comes from the need to transfer data efficiently, reliably and flexibly in control and monitoring systems operating in various environments. In spite of the widespread and great success that wireless systems have made in control environments, wiring is still indispensable. Therefore it is useful to integrate wired and wireless technologies to overcome the disadvantages of the two systems, take advantage of each other’s, and integrate the various components of the control system (sensors, actuators, microcontroller). this research aims to study and design a hybrid (wired / wireless) gateways to connect the hybrid parts ,ZigBee and CAN, of the data transfer network that is used in control and monitoring environments, based on the wired CAN Bus technology at the partial networks level and connect this nets by using a wireless backbone based on ZigBee technology. In order to link the two hybrid protocols CAN and ZigBee, a common application layer , that supports the transfer of frames crossing between the two protocols, was designed, Its main function is to aggregate and disaggregate messages, using the OMNeT++ networking simulator to evaluate and compare results. تأتي أهمية الدمج بين تقنيات الاتصالات المختلفة من ضرورة نقل المعطيات بفعالية ووثوقية ومرونة وخاصة في أنظمة التحكم والمراقبة العاملة في البيئات الزراعية والصناعية والخدمية المتنوعة. على الرغم من أن الأنظمة اللاسلكية قد حققت رواجاً هائلاً في بيئات التحكم المختلفة, إلا أنه لا يمكن الاستغناء عن الربط باستخدام الأسلاك. لذلك كان من المفيد أن ندمج بين التقنيات السلكية واللاسلكية, وذلك للتغلب على عيوب النظامين, والاستفادة من مزايا كل منهما , وتحقيق التكامل بين مكونات نظم التحكم المختلفة (حساسات ,مشغلات, متحكمات). يهدف هذا البحث إلى دراسة وتصميم بوابة هجينة )سلكية/لاسلكية( لربط الأجزاء الهجينة(CAN - ZigBee ) من شبكة هجينة مناسبة لنقل المعطيات في بيئات التحكم والمراقبة، باستخدام الناقل السلكي CAN Bus على مستوى الشبكات الجزئية وربط هذه الشبكات باستخدام عمود فقري Backbone لاسلكي , يعتمد على تقنية ZigBee. حيث تم اقتراح تصميم طبقة تطبيق مشتركة تدعم بوابة عبور الأطر بين البروتوكولين , وظيفتها الأساسية هي تجميع وفك تجميع الرسائل, ومن ثم محاكاة الشبكة السابقة باستخدام المحاكي الشبكي OMNeT++ ومن ثم استخلاص النتائج ومقارنتها .